TRANSFORMASI DAN INOVASI KOLOTOK MENJADI ALAT MUSIK BAMBU DALAM KOMPOSISI KOLOTOUCH: TRANSFORMASI DAN INOVASI KOLOTOK MENJADI ALAT MUSIK BAMBU DALAM KOMPOSISI KOLOTOUCH - -, Farhan Setiawan; I Komang Kusuma Adi; Satria Mulya (Awilaras, 2025)
Kolotok, originally a livestock marker used in rice fields, has been increasingly marginalized due to modern technological advances that replace cattle and buffalo with mechanical plowing. The disappearance of its distinctive sound has not only silenced the dynamic atmosphere of the paddies but also eroded the agrarian cultural identity of the Ciamis community. This study aims to explore the transformation and innovation of kolotok into a new bamboo musical instrument through the composition “Kolotouch”. The method combines field observation, organological experimentation, acoustic measurement, and the application of Pande Made Sukerta’s text and context theory. The result is the Kolbam, a modified kolotok with a bamboo tube design that produces unique timbres according to the chamber size, integrated into modern bamboo music repertoire. This creation demonstrates that local instrument innovation can revive agrarian cultural values while enriching contemporary musical expression.